Листування Юрія Лавріненка з Юрієм Шерехом у 1945–1949 роках (Підготовка й коментарі Тетяни Шестопалової) (Слово і Час, 2012)
Продовження публікації листів Ю. Лавріненка та Ю. Шереха один до одного під час
перебування в Західній Європі (Німеччина, Австрія, 1945–1949). Подано листи 1946 й частково
1947 р., які зберігаються в Музеї-Архіві УВАН у Нью-Йорку. Кореспонденція висвітлює факти
внутрішньолітературних протистоянь у період МУРу, подає відверті характеристики подій та
осіб, причетних до української літератури в ДіПі-таборах, збагачує уявлення про стан української
еміграційної періодики на той час. This is the second part of the publication which offers the correspondence between Yu. Lavrinenko
and Yu. Sherekh during their stay in Western Europe (Germany, Austria, 1945–1949). It contains the
letters from 1946 and in part from 1947 stored in the archives of the UVAN (Ukrainian Free Academy
of Sciences) in New York. The correspondence sheds light on the inner confl icts in the literary circles
during the period of the so-called “MUR” – “Mystetsky Ukrayinsky Rukh” (Ukrainian Artistic Movement),
provides rather outspoken characteristics of the events and persons who continued to be
concerned about Ukrainian literature, even in DP camps, and also enriches our notion of the émigré
periodicals of that time. Продолжение публикации писем Ю. Лавриненко и Ю. Шереха
друг к другу во время их пребывания в Западной Европе
(Германия, Австрия, 1945–1949). Представлены письма 1946 и
частично 1947 года, сохранившиеся в Музее-Архиве УВАН в Нью-
Йорке. Корреспонденция освещает факты внутрилитературных
противостояний в период МУРа (“Артистического украинского
движения”), содержит откровенные характеристики событий и
личностей, причастных к украинской литературе в ДиПи-лагерях,
обогащает представление об украинской эмиграционной периодике
того времени.